2021
DOI: 10.3389/fonc.2021.644645
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors and Cumulative Risk Analysis of Cervical Lymph Node Metastasis of Papillary Thyroid Microcarcinoma

Abstract: ObjectiveTo explore the influencing factors and cumulative risk of lymph node metastasis (LNM) in papillary thyroid microcarcinoma (PTMC) patients.Methods607 patients confirmed PTMC pathologically after thyroidectomy were enrolled in this retrospective study. The rate of LNM was calculated. Different clinicopathological characteristics were compared in PTMC patients with and without LNM and in different subgroups of LNM, respectively. Correlation between clinicopathological characteristics and LNM was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 51 publications
1
10
3
Order By: Relevance
“…This suggests that lateral LNs are more commonly involved, especially for occult metastasis. This is different from previous studies, where central LNs were the most common area for LNM [ 15 , 21 , 39 ]. This result of a high rate of LLNM and occult LLNM could help surgeons in the decision of performing prophylactic lateral lymph node dissections to reduce recurrence.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…This suggests that lateral LNs are more commonly involved, especially for occult metastasis. This is different from previous studies, where central LNs were the most common area for LNM [ 15 , 21 , 39 ]. This result of a high rate of LLNM and occult LLNM could help surgeons in the decision of performing prophylactic lateral lymph node dissections to reduce recurrence.…”
Section: Discussioncontrasting
confidence: 96%
“…In the present study, we analyzed the retrospective data of 226 patients with PTMC. The results revealed that the rate of LNM was 43.8%, which is within the range previously reported [ 15 , 38 ]. The rate of CLNM was 17.7% and LLNM was 26%.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, Xue et al 67 suggest that HT is protective against recurrence. However, Yin et al 68 show that HT is independently and positively linked to LNM in female PTMC patients aged <55 years. HT was not a significant risk factor for hv‐CLNM in PTMC patients herein.…”
Section: Discussionmentioning
confidence: 97%